Effect of natural antioxidants in Spanish salchichón elaborated with encapsulated n-3 long chain fatty acids in konjac glucomannan matrix. (February 2017) - Munekata, P.E.S.; Domínguez, R.; Franco, D.; Bermúdez, R.; Trindade, M.A.; Lorenzo, Jose M.
Abstract: The effect of natural antioxidants on physicochemical properties, lipid and protein oxidation, volatile compounds and free fatty acids (FFA) were determined in Spanish salchichón enriched with n -3 fatty acids encapsulated and stabilized in konjac matrix. Phenolic compounds of beer residue extract (BRE), chestnut leaves extract (CLE) and peanut skin extract (PSE) were also identified and quantified. Five batches of salchichón were prepared: control (CON, without antioxidants), butylated hydroxytoluene (BHT), BRE, CLE and PSE. The main phenolic compounds were catechin and benzoic acid for BRE, gallic acid and catechin for CLE and catechin and protocatechuic acid for PSE. Statistical analysis did not show significant differences on chemical composition among treatments. Reductions in luminosity (P  < 0.05) and pH ( P  < 0.001) were observed with the CLE batch, whereas the other colour parameters were not affected by the addition of natural antioxidants. Finally, the inclusion of antioxidants ( P  < 0.001) decreased the hexanal content, whereas the FFA content increased by the addition of natural extracts. Highlights: Natural antioxidants reduce protein oxidation. Free fatty acids content were higher in antioxidant batches. Natural antioxidants had low effect in comparison with BHT. Natural antioxidants reduce lipid-derive volatiles.